Field notes contributed by Beth Proescholdt, spring 1982 - Proescholdt, Bethet al (1982)
Field notes were contributed by Beth Proescholdt and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed